PENGEMBANGAN APLIKASI SEWA LAPAK PASAR (e-Selapas) BERBASIS WEBSITE UNTUK KEMUDAHAN TRANSAKSI RETRIBUSI PADA PASAR WAGE KABUPATEN BANYUMAS - Vembria Rose Handayani; Sutrisno Sutrisno; Luthfi Febriyanti; Farhah Amalia Yantika (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
A market is an area where interaction occurs between buyers and sellers to carry out buying and selling activities of goods or services. And the market also functions as an economic center, the market regulates economic activities and plays an important role in driving economic growth. In Pasar Wage, Banyumas Regency, the process of payment transactions for market stall rental fees and the use of information technology have not been optimized. Management of market stall rental fee data is still done manually. Officers must go around visiting stalls to collect market stall rental fees from traders. Officers must always check or cross-check which traders have paid the stall rental fee and which have not. The use of tickets can be done paperless to reduce paper use as one of the go green movements. Thus, a website-based market stall rental fee payment information system application was created to overcome these problems. In developing this application, the Fountain Method is used as a system development method and PHP is used as a programming language. And MySQL for database management. This system is expected to facilitate traders in conducting market stall rental fee payment transactions and officers to make market stall rental fee withdrawal transactions, manage transaction data, and produce market stall rental fee reports more quickly, accurately, effectively, and efficiently.